Impact of extended trading hours in market microstructure: evidence from the Kuala Lumpur stock exchange - Gan, Seow Cheng (2015)
This study investigates the impact of extended trading hours on market microstructures as measured by market volatility, trading volume, autocorrelation coefficients and the speed of price adjustment to new information. Based on the daily observations for the KLSE index from 28 January 1992 to 31 December 1992, this study finds that the Kuala Lumpur market has not showed mark improvement in its market efficiency except for its trading volume, after it extended its trading hours by 90 minutes. The market volatility analysis using Parkinson variance method, indicates an increase of 1. 68% from Subperiod I (28/11/92 - 21/7/92) to Subperiod II (22/7/92 - 31/12/92) in market volatility. As for trading volume, it has shown a substantial increase of 2.72 times more after its extension of trading hours. Last but not least, the analysis on both autocorrelation coefficients and price adjustment show that the Kuala Lumpur stock market has not improved substantially on processing market-wide information despite the additional trading hours.